Hari Farmasis Sedunia: Penyuluhan Informasi Obat dan Pembagian Masker Gratis di Kampung Seraya Batu Ampar Batam - Delladari Mayefis; Sri Hainil; Hidayati Hidayati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
World Pharmacists day is an annual event to commemorate World Pharmacist Day. One form of our participation in the Bachelor of Pharmacy STIKes study program Mitra Bunda Persada Batam in celebrating the World Pharmacist Day is to hold information on drug information as well as free mask distribution for residents in Seraya Batu Ampar village. This free mask distribution is because in recent months there have been forest fires that have caused air pollution in Batam City. The World Pharmacist Day program was held in September 2015 with Drug Information Services for residents and free mask distribution for motorists on the streets around the village while. The program began in the morning, which started with a question and answers from the residents about the drugs they were using, then continued with the distribution of masks. This event was very well received by the residents because it was scarce for an event like this to be done. Our Pharmacy Study Program is very enthusiastic about being able to provide community service